Long‐term outcomes of cancer‐related isolated distal deep vein thrombosis: the OPTIMEV study. (21st April 2017) - Galanaud, J.‐P.; Sevestre, M.‐A.; Pernod, G.; Genty, C.; Richelet, S.; Kahn, S. R.; Boulon, C.; Terrisse, H.; Quéré, I.; Bosson, J.‐L.
Abstract : Essentials Clinical significance of cancer‐related isolated distal deep vein thrombosis (iDDVT) is unknown. We studied patients with iDDVT, with and without cancer, and proximal DVT with cancer. Cancer‐related iDDVT patients have a much poorer prognosis than iDDVT patients without cancer. Cancer‐related iDDVT patients have a similar prognosis to cancer‐related proximal DVT patients. Summary: Background: Isolated distal deep vein thrombosis (iDDVT) (infra‐popliteal DVT without pulmonary embolism [PE]) is a frequent event and, in the absence of cancer, is usually considered to be a minor form of venous thromboembolism (VTE). However, the clinical significance of cancer‐related iDDVT is unknown. Methods: Using data from the observational, prospective multicenter OPTIMEV cohort, we compared, at 3 years, the incidences of death, VTE recurrence and major bleeding in patients with cancer‐related iDDVT with those in cancer patients with isolated proximal DVT (matched 1:1 on age and sex) and patients with iDDVT without cancer (matched 1:2 on age and sex). Results: As compared with patients with cancer‐related isolated proximal DVT ( n = 92), those with cancer‐related iDDVT ( n = 92) had a similar risk of death (40.8% per patient‐year (PY) vs. 38.3% per PY; aHR = 1.0, 95% CI[0.7–1.4]) and of major bleeding (3.8% per PY vs. 3.6% per PY, aCHR = 0.9 [0.3–3.2]) and a higher risk of VTE recurrence (5.4% per PY vs. 11.5% per PY; aCHR = 1.8 [0.7–4.5]). As compared with patients with iDDVT without cancer ( n = 184), those with cancer‐related iDDVT had a nine times higher risk of death (3.5% per PY vs. 38.3% per PY; aHR = 9.3 [5.5–15.9]), a higher risk of major bleeding (1.8% per PY vs. 3.6% per PY; aCHR = 2.0 [0.6–6.1]) and a higher risk of VTE recurrence (5.0% per PY vs. 11.5% per PY; aCHR = 2.0 [1.0–3.7]). The results remained similar in the subgroup of patients without history of VTE. Conclusion: Patients with cancer‐related iDDVT seem to have a prognosis that is similar to that of patients with cancer‐related isolated proximal DVT and a dramatically poorer prognosis than patients with iDDVT without cancer. This underlines the high clinical significance of cancer‐related iDDVT and the need for additional studies.